Heart failure in the general population and impact of the 2021 European Society of Cardiology Heart Failure Guidelines. (20th April 2022) - Wenzel, Jan‐Per; Nikorowitsch, Julius; bei der Kellen, Ramona; Magnussen, Christina; Bonin‐Schnabel, Renate; Westermann, Dirk; Twerenbold, Raphael; Kirchhof, Paulus; Blankenberg, Stefan; Schrage, Benedikt
Abstract: Aim: The diagnosis of heart failure (HF) has been refined in several steps in recent years, reflecting evolving diagnostic and therapeutic approaches. The European Society of Cardiology (ESC) recently published a modified definition of HF in the 2021 heart failure (HF) guidelines. The impact of this new diagnostic algorithm on the prevalence of HF is not known. The aim of this study was to describe the contemporary prevalence of HF in a representative, completely phenotyped sample from the general population. Methods and results: This analysis was conducted among 7074 participants (aged 45–78 years, 51.5% women) from the population‐based Hamburg City Health Study . Compared with the 2016 version, HF prevalence increased with the 2021 HF guidelines from 4.31% to 4.83% (12% increase). This increase was driven by a higher number of subjects with HF with reduced/mildly‐reduced ejection fraction (0.47% to 0.52%; 1.37% to 2.12%), while the number of subjects with HF with preserved ejection fraction decreased from 2.46% to 2.19%. Importantly, this did not impact the known risk factor profiles of the phenotypes. Although four drugs are recommended for all subjects with HFrEF in the new guidelines, several adjunctive therapies are recommended for dedicated cases/scenarios (e.g. <1% eligibility for ivabradine/vericiguat/devices). Conclusion: Heart failure remains common in a contemporary general population sample. The number of patients with HF will increase when the current diagnostic criteria are applied. This offers opportunities to initiate preventive therapies, especially in patients with HFmrEF and HFrEF.